A Phase 1 Study of IRX195183, a RARα-Selective CYP26 Resistant Retinoid, in Patients With Relapsed or Refractory AML - Ambinder, Alexander J.; Norsworthy, Kelly; Hernandez, Daniela; Palau, Laura; Paun, Bogdan; Duffield, Amy; Chandraratna, Rosh; Sanders, Martin; Varadhan, Ravi; Jones, Richard J.; Douglas Smith, B.; Ghiaur, Gabriel (Frontiers in Oncology, 2020)
Subsets of non-acute promyelocytic leukemia (APL) acute myelogenous leukemia (AML) exhibit aberrant retinoid signaling and demonstrate sensitivity to retinoids in vitro. We present the results of a phase 1 dose-escalation study that evaluated the safety, pharmacodynamics, and efficacy of IRX195183, a novel retinoic acid receptor α agonist, in patients with relapsed or refractory myelodysplastic syndrome (MDS) or AML. In this single center, single arm study, eleven patients with relapsed or refractory MDS/AML were enrolled and treated. Oral IRX195183 was administered at two dose levels: 50mg daily or 75mg daily for a total of two 28 day cycles. Patients with stable disease or better were allowed to continue on the drug for four additional 28 day cycles. Common adverse events included hypertriglyceridemia, fatigue, dyspnea, and edema. Three patients at the first dose level developed asymptomatic Grade 3 hypertriglyceridemia. The maximally tolerated dose was not reached. Four of the eleven patients had (36%) stable disease or better. One had a morphological complete remission with incomplete hematologic recovery while on the study drug. Two patients had evidence of in vivo leukemic blast maturation, as reflected by increased CD38 expression. In a pharmacodynamics study, plasma samples from four patients treated at the lowest dose level demonstrated the capacity to differentiate leukemic cells from the NB4 cell line in vitro. These results suggest that IRX195183 is safe, achieves biologically meaningful plasma concentrations and may be efficacious in a subset of patients with MDS/AML.